Applying internet laws and regulations to educational technology - Mann, Bruce Leslie 1950 (Advances in public policy and administration (APPA) book series, 2020)
"This book describes an emerging sub-discipline, educational technology law. It focuses on the obligations of various stakeholders in educational technology and the different forms of lawful protection afforded to teachers and students under technology law"-- c Provided by publisher